Broad complex and wing development in cockroaches. (August 2022) - Fernandez-Nicolas, Ana; Ventos-Alfonso, Alba; Kamsoi, Orathai; Clark-Hachtel, Courtney; Tomoyasu, Yoshinori; Belles, Xavier
Abstract: In hemimetabolan insects, the transcription factor Broad complex (Br–C) promotes wing growth and development during the nymphal period. We wondered whether Br–C could trigger the initiation of wing development, using the cockroach Blattella germanica as a model. We show that first instar nymphs have their unique identity of these three thoracic segments specified. During embryogenesis, the expression of Br–C and some wing-related genes show two matching waves. The first takes place before the formation of the germ band, which might be involved in the establishment of various developmental fields including a potential "wing field", and the second wave around organogenesis, possibly involved in the initiation of wing development. However, the expression of Br–C in early embryogenesis concentrates in the developing central nervous system, thus not co-localizing with the expression of the typical wing-related gene vestigial, which is expressed at the edge of the thoracic and abdominal segments. This suggests that Br–C is not specifically involved in the establishment of a potential "wing field" in early embryogenesis. Moreover, maternal RNAi for Br–C depletes the first wave of Br–C expression but does not affect the early expression of wing-related genes. As maternal Br–C RNAi did not deplete the second expression wave of Br–C, we could not evaluate if Br–C is involved in the initiation of wing development. Alternatively, using nymphal RNAi of Br–C and Sex combs reduced ( Scr ), we show that Br–C contributes to the formation of ectopic wing structures that develop in the prothorax when Scr is depleted. The gene most clearly influenced by Br–C RNAi is nubbin ( nub ), which, in nymphs is crucial for wing growth. Together, these results suggest that Br–C does not specifically contribute to the establishment of the "wing field", but it does seem important later, in the initiation of wing development, enhancing the expression of wing-related genes, especially nub . This supports the hypothesis previously proposed by the authors, whereby Br–C might have facilitated the evolution of holometaboly. However, there is no doubt that other factors have also contributed to this evolution. Graphical abstract: Image 1 Highlights: Blattella germanica embryos express Br–C in respective waves at early and mid stage. Expression of wing-related genes follows a pattern similar to that of Br–C . Br–C may be involved in the initiation of wing development at mid embryogenesis. In nymphs, Br–C contributes to the growth of ectopic wing structures in the prothorax. In nymphs, Br–C enhances the expression of nubbin, promoting meso- and metathoracic wing growth.